FORMATION AND DEVELOPMENT OF READING NEEDS BASED ON SECONDARY SOURCES OF INFORMATION (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
The article reveals the features of the bibliographic activity of the Alisher Navoi National Library of Uzbekistan in the preparation of secondary sources of information that contribute to meeting the diverse information needs of readers